2014
DOI: 10.1016/j.schres.2014.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Impaired insight into illness and cognitive insight in schizophrenia spectrum disorders: Resting state functional connectivity

Abstract: Background Impaired insight into illness (clinical insight) in schizophrenia has negative effects on treatment adherence and clinical outcomes. Schizophrenia is described as a disorder of disrupted brain connectivity. In line with this concept, resting state networks (RSNs) appear differentially affected in persons with schizophrenia. Therefore, impaired clinical, or the related construct of cognitive insight (which posits that impaired clinical insight is a function of metacognitive deficits), may reflect alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 82 publications
6
52
1
2
Order By: Relevance
“…Vohs et al 11 reported robust correlations between metacognitive capacity and multiple domains of clinical insight, as well as the self-certainty domain of cognitive insight, in first-episode psychosis. These findings are consistent with imaging studies which suggest that insight is related to cortical regions and circuits that may support processes necessary for metacognition, including self-consciousness and self-referential processing 102 .…”
Section: Metacognition As a Root Of Poor Insightsupporting
confidence: 90%
See 2 more Smart Citations
“…Vohs et al 11 reported robust correlations between metacognitive capacity and multiple domains of clinical insight, as well as the self-certainty domain of cognitive insight, in first-episode psychosis. These findings are consistent with imaging studies which suggest that insight is related to cortical regions and circuits that may support processes necessary for metacognition, including self-consciousness and self-referential processing 102 .…”
Section: Metacognition As a Root Of Poor Insightsupporting
confidence: 90%
“…Consistent with this, studies employing both structural 99 and functional [100][101][102][103][104][105] neuroimaging have implicated a number of areas and networks in the development and maintenance of insight.…”
Section: Abnormalities In Brain Function As a Root Of Poor Insightmentioning
confidence: 65%
See 1 more Smart Citation
“…Moreover, chronic schizophrenia is associated with more high-frequency fluctuation and less low-frequency fluctuation in the DMN than healthy volunteers when performing the auditory oddball task [36], which is consistent with the subsequent findings of fluctuation in the DMN they reported in different CSP samples and controls [37]. Work by Gerretsen et al [51] and Table 1 Summary of empirical studies on DMN activity and connectivity in schizophrenia. MSI, multi-source interference; SPT, semantic priming task; FEE, facial emotional expressions; SRT, self-reflection task; SAT, selective attention task; HFF, high-frequency fluctuations; LFF, low-frequency fluctuations; PS, positive symptom; NS, negative symptom; CF: cognitive function; DMN, default mode network; PCC, posterior cingulate cortex; PCUN, precuneus; IFG, inferior frontal gyri; LPL, lateral parietal lobe; IPL, inferior parietal lobe; MPFC, medial prefrontal cortex; PFC, prefrontal cortex; vmPFC, ventromedial prefrontal cortex; DPFC, dorsolateral prefrontal cortex; ACC, anterior cingulate cortex; PHG, parahippocampal gyri; (-) not tested; (:) for resting fMRI, increased activation; for task fMRI, increased deactivation; (;) for resting fMRI, decreased activation; for task fMRI, reduced deactivation; (NS) not significant; (*) relationship between DMN activity/deactivation (or connectivity) and particular behavioral measures; (**) group differences of schizophrenia patients versus controls; (***) patient group includes patients in the early phase of schizophrenia, schizoaffective and schizophreniform disorder; (****)…”
Section: Functional Connectivity In the Dmn In Schizophreniasupporting
confidence: 83%
“…A similar pattern has been observed in individuals early in the course of schizophrenia, as their ability to recognize and respond to psychological and social challenges was shown to be predictive of clinical insight [30]. These findings are consistent with imaging studies that suggest insight is related to structure and function in brain areas or circuits thought to support processes necessary for metacognition, including self-consciousness, self-other distinction, and self-referential procession [95][96][97][98][99].…”
Section: Deficits In Social Cognition and Poor Metacognitionsupporting
confidence: 80%